Effects of photoperiod on reproduction of Siamese fighting fish Betta splendens - Giannecchini, Luiz Gustavo [UNESP]; Massago, Haluko [UNESP]; Fernandes, João Batista Kochenborger [UNESP] (Sociedade Brasileira de Zootecnia, 2012)
This study investigated the effect of different photoperiods (24 h of light (L):0 h of darkness (D); 20L:4D; 16L:8D; 12L:12D; and 8L:16D) on the reproduction and growth of Betta splendens. The results showed that spawning frequency was significantly higher in couples reared under 16L:8D and 12L:12D, in comparison with other treatments. The highest number of eggs per spawn was obtained under 16L:8D (544.76±375.23) and 12L:12D (471.13±261.52), and the lowest values were detected for 24L:0D (128.55±58.14) and 20L:4D (187.87±103.84). Fertility and fecundity also showed significantly higher average values in 16L:8D and 12L:12D when compared with 24L:0D and 20L:4D treatments. Egg volume and perivitelline space were significantly higher in 24L:0D treatments that showed the lowest numbers of eggs per spawn, while the vitelline volume did not show significant differences. Other variables such as breeders weight gain and condition factor (K) were not statistically different. Moreover, the final length varies according to photoperiod and gender. These results demonstrated a key role for the photoperiod upon B. splendens reproduction. The best reproductive performance is achieved under the photoperiods that best approached those that occur in spring and summer (16L:8D and 12L:12D), coinciding with their best seasons for reproduction.
Keywords: egg production; fertility; light regimen; ornamental fish